Prevalence of sarcopenia in community‐dwelling older people of Mexico City using the EGWSOP (European Working Group on Sarcopenia in Older People) diagnostic criteria. Issue 2 (1st July 2017) - Espinel‐Bermúdez, María Claudia; Ramírez‐García, Eliseo; García‐Peña, Carmen; Salvà, Antoni; Ruiz‐Arregui, Liliana; Cárdenas‐Bahena, Ángel; Sánchez‐García, Sergio
Abstract: Background: The aim of this study is to determine the prevalence of sarcopenia in community‐dwelling older people living in Mexico City using the EGWSOP (European Working Group on Sarcopenia in Older People) diagnostic criteria that include muscle mass, muscle strength and physical performance. Methods: The sample population was based on older people (≥60 years) affiliated with the Mexican Institute of Social Security in Mexico City. Data were derived from the database of the "Cohort of Obesity, Sarcopenia and Frailty of Older Mexican Adults" (COSFOMA). Sarcopenia was diagnosed using the EGWSOP criteria: gait speed (4 m) <0.8 m/s; handgrip strength (using a dynamometer) <20 kg in women or <30 kg in men, and muscle mass index (MMI) <6.1 kg/m 2 in women or <8.5 kg/m 2 in men (using bioelectrical impedance analysis, BIA). Results: Thousand hundred seventy‐seven subjects were included (median age 68.4 years, 60.2% women). 20.5% had low gait speed (19.1% women and 22.6% men); 62.4% had low handgrip strength (69.9% women and 51.2% men) and 12.3% had low muscle mass (9.9% women and 16.0% men). Only 9.9% of older people with sarcopenia (9.0% women and 11.1% men): 1.9% with severe sarcopenia (1.4% women and 2.6% men) and 8.0% with moderate sarcopenia (7.6% women and 8.5% men). Conclusions: Sarcopenia is present in one of ten community‐dwelling older people residing in Mexico City. According to what has been reported in the literature, the prevalence of sarcopenia in older Mexican adults is similar to the community‐dwelling population.